Optimalisasi Pemberdayaan Organisasi Siswa di Sekolah Sebagai Upaya Pencegahan Kekerasan Seksual - Masruroh, Masruroh; Sulistyawati, Arum Kurnia; Setyaningsih, Dewi; Solihin, Mohammad; Anjelika, Marseli Dwi; Yanggu, Frisca Priscilla Leda; Setiyawan, Robin (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This service activity aims to increase students' knowledge and skills in preventing and handling sexual violence by the Regulation of the Minister of Religion of the Republic of Indonesia No. 73 of 2022 by optimizing school organizations' empowerment. This service partner was the school organization at MAN 2 Sleman Yogyakarta. The method for implementing this service used Focus Group Discussion (FGD) and training in the form of lectures, case studies and roleplay. The data analysis technique for this service used descriptive analysis. The service results showed that the characteristics of participants based on gender showed that the ratio of male participants was 25% greater than that of female participants. After the training, there was an increase in knowledge and skills related to hard skills and soft skills in preventing sexual violence in the school environment by 18.75% of participants who got a score of 100 and an increase of 12.50% of participants who got a score of 90. It showed that this training program had a positive impact and increases knowledge of hard skills and soft skills in preventing sexual violence in the school environment.